Deterministic Photon Storage and Readout in a Semimagnetic Quantum Dot–Cavity System Doped with a Single Mn Ion. Issue 4 (27th January 2022) - Cosacchi, Michael; Seidelmann, Tim; Mielnik‐Pyszczorski, Adam; Neumann, Miriam; Bracht, Thomas K.; Cygorek, Moritz; Vagov, Alexei; Reiter, Doris E.; Axt, Vollrath M.
Abstract: Light trapping is a crucial mechanism for synchronization in optical communication. Especially on the level of single photons, control of the exact emission time is desirable. In this paper, a single‐photon buffering device composed of a quantum dot doped with a single Mn atom in a cavity is theoretically proposed. A method to detain a single cavity photon as an excitation of the dot is presented. The storage scheme is based on bright to dark exciton conversion performed with an off‐resonant external optical field and mediated via a spin‐flip with the magnetic ion. The induced Stark shift brings both exciton states to resonance and results in an excitation transfer to the optically inactive one. The stored photon can be read out on demand in the same manner by repopulating the bright state, which has a short lifetime. The results indicate the possibility to suspend a photon for almost two orders of magnitude longer than the lifetime of the bright exciton. Abstract : Synchronization in optical communication is paramount. To this end, buffering devices are desirable, in particular, on the single‐photon level. A single‐photon storage protocol in a solid‐state quantum‐dot–cavity system is proposed. The quantum dot is doped with a single Mn atom that facilitates a coupling between the bright and the dipole dark excitons. The latter is a metastable state, where the photon is buffered as an electronic excitation.